2020
DOI: 10.30659/e.5.2.251-262
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in santri�s reading attitude and motivation

Abstract: A considerable amount of studies has explored gender differences in reading attitude and motivation among students in both elementary and secondary school levels. However, none of them is concerned with English reading attitude and motivation among santri or students living at Islamic boarding school in which gender segregation is applied. This study attempts to investigate santri�s reading attitude and reading motivation based on their gender. Three hundred and nineteen students at pesantren-based senior high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Several research have already conducted the same nature of investigation to improve instruction and assist learning (Tomlinson et al, 2002) For example, a study by Rachmajanti and Musthofiyah (2017) found out about a pattern of relationships based on gender difference, reading efficacy, comprehension, and attitude; the results are recommended as basis to predict EFL reading achievement. Results in another study specifically revealed that female students had higher reading attitude and motivation than male students (Murtafi'ah et al, 2020). However, this is in contrast with the findings of Sinha and Gupta (2007) where they concluded that preschool boys scored higher than girls on the recreational reading attitude measure.…”
Section: Introductionmentioning
confidence: 74%
“…Several research have already conducted the same nature of investigation to improve instruction and assist learning (Tomlinson et al, 2002) For example, a study by Rachmajanti and Musthofiyah (2017) found out about a pattern of relationships based on gender difference, reading efficacy, comprehension, and attitude; the results are recommended as basis to predict EFL reading achievement. Results in another study specifically revealed that female students had higher reading attitude and motivation than male students (Murtafi'ah et al, 2020). However, this is in contrast with the findings of Sinha and Gupta (2007) where they concluded that preschool boys scored higher than girls on the recreational reading attitude measure.…”
Section: Introductionmentioning
confidence: 74%
“…This self-potential analysis must be understood, that these students often have innate potential/talents, such as the ability to read the Qur'an, music, calligraphy, plantations, carpentry, and so on (Yayasan Santrendelik Kampung Tobat, 2021a). This innate talent should always be nurtured and developed (Murtafi'ah & Putro, 2020). Islamic boarding schools need to develop a forum for the appreciation of Santri's Lifeskill to explore and explore the potential of students, this kind of forum already exists in several Islamic boarding schools, one of which is the Santrendelik Islamic boarding school.…”
Section: Introductionmentioning
confidence: 99%